Pengaruh model NHT (Number Heads Together) berbantuan media “LEMDAWA” terhadap kemampuan pemahaman konsep matematika kelas III di SDI Asshodiqiyah - Eka Wulanningrum (COLLASE (Creative of Learning Students Elementary Education), 2023)
This quasi-experimental research aims to determine the effect cooperative learning type NHT ( Number Heads Together ) on understanding student mathematics. This research This research is a kind of research is pre-experimental. While the form of the design is "pre-test and post-test one group design" namely research which only uses one experimental class without any class comparison or control class. The research population was all third grade students in the even semester of SDI Asshodiqiyah academic year 2022/2023. The population in this study were Grade III Asshodiqiyah Elementary School students with techniques Nonrandom Samplingwith the type of saturated sampling technique, the sample is class III as an experimental class. Based on Data analysis used is the one-way analysis of variance test. The results of the One Sample Test t test on the post test, the value of t count > t table is 2,966 > 2.052, then HI is accepted and H0 is rejected. So it can be concluded that there isthe influence of the NHT ( Number Heads Together ) model assisted by the media "LEMDAWA" on the ability to understand mathematical concepts of class III students at SDI Asshodiqiyah. The results of the sig. 0.006 < 0.05 then H0 is rejected so it can concluded that there is an influence of the NHT ( Number Heads Together ) model assisted by the media "LEMDAWA" with the ability to understand concepts mathematics class III SDI Asshodiqiyah.Keywords : number heads together, understanding of mathematical concepts, learning media